Towards adapting the consensus proof of authentication algorithm for IoT - Mohamed Aghroud; Yassin El Gountery; Mohamed Oualla; Lahcen El Bermi (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The Internet of Things (IoT) represents an increasingly sophisticated paradigm which interconnects heterogeneous devices, enabling continuous data exchange and automation. However, IoT systems face significant challenges related to scalability, limited device resources, and data security. Blockchain technology provides an effective foundation for addressing such challenges thanks to its decentralized structure and consensus algorithms. This work focuses on improving the blockchain consensus protocol or consensus algorithm referred to as proof of authentication (PoAh) for adaptation to IoT networks using smart contract. It also presents a comparison of various existing consensus algorithms and explores different blockchain open-source platforms and their adaptation to IoT. Although experimental validation remains part of future work, the conceptual design and theoretical analysis presented here lay the groundwork for the future implementation and evaluation of the improved PoAh within real IoT use cases.